Scanner-Assisted CO2 Laser Fissurectomy: A Pilot Study - Giani, Iacopo; Cioppa, Tommaso; Linari, Chiara; Caminati, Filippo; Dreoni, Paolo; Rossi, Gianni; Tanda, Cinzia; Talamo, Giuseppina; Bettazzi, Federico; Aprile, Alessandra; Grassi, Silvia; Pede, Antonella; et al. (Frontiers in Surgery, 2021)
Introduction Surgery for Chronic anal fissure is challenging. Solving the pain by guaranteeing rapid and effective healing is the objective, but what is the price to pay today in functional terms? Though this result is nowadays partially achievable through interventions that include the execution of an internal sphincterotomy among the procedures, it is necessary to underline the high rate of postoperative fecal incontinence. Aim of this study is to explore the effectiveness of Scanner-assisted CO2 Laser Fissurectomy. Methods From April 2021 to September 2021, all consecutive patients affected by chronic anal fissure suitable for surgery, meeting the inclusion and exclusion criteria were evaluated. All planned data were recorded before surgery, at 24 hours, 1 week and 1. A scanner-assisted CO2 Laser was used in this study to achieve a smooth and dried wound with a minimal tissue thermal damage, in order to ensure good post-surgical pain control, rapid and functional, elastic and stable healing, and to prevent potential relapses. Paracetamol 1g every 8 hours was prescribed for the first 24 hours and then continued according to each patients need. Ketorolac 15mg was prescribed as rescue. Results Mean pain intensity≤3, considered as the principal endpoint, was recorded in 26 out of the 29 patients enrolled in the study with a final success rate of 89,7% at 1 month follow up. Pain and anal itching showed a statistically significant reduction while bleeding, burning, maximum pain and REALIS score showed a reduction too at the end of the follow-up period. Re-epithelization proved to be extremely fast and effective: 22 of 29(75,9%) showed a complete healing and 5 a partial re-epithelization at 1 month follow up . Discussion Outcomes of this study showed that it is undoubtedly necessary to change the surgical approach in case of anal fissure. , the internal sphincterotomy procedure must be most of all questioned, where the availability of cutting-edge technological tools must be avoided and offered only in selected cases. Scanner-assisted CO2 Laser showed great results in terms of pain control and wound healing, secondary to an extremely precise ablation, vaporization and debridement procedures with minimal lateral thermal damage.